Vaccinating for natural killer cell effector functions. Issue 1 (31st January 2018) - Wagstaffe, Helen R; Mooney, Jason P; Riley, Eleanor M; Goodier, Martin R
Abstract: Vaccination has proved to be highly effective in reducing global mortality and eliminating infectious diseases. Building on this success will depend on the development of new and improved vaccines, new methods to determine efficacy and optimum dosing and new or refined adjuvant systems. NK cells are innate lymphoid cells that respond rapidly during primary infection but also have adaptive characteristics enabling them to integrate innate and acquired immune responses. NK cells are activated after vaccination against pathogens including influenza, yellow fever and tuberculosis, and their subsequent maturation, proliferation and effector function is dependent on myeloid accessory cell‐derived cytokines such as IL‐12, IL‐18 and type I interferons. Activation of antigen‐presenting cells by live attenuated or whole inactivated vaccines, or by the use of adjuvants, leads to enhanced and sustained NK cell activity, which in turn contributes to T cell recruitment and memory cell formation. This review explores the role of cytokine‐activated NK cells as vaccine‐induced effector cells and in recall responses and their potential contribution to vaccine and adjuvant development. Abstract : Activation of Natural Killer (NK) cell function by vaccines. Whole organism live‐attenuated or adjuvanted subunit vaccines against a range of pathogens stimulate NK cell activation by induction of innate cytokines from accessory cells. Antigen‐specific T cells and antibodies promote NK cell function on secondary booster vaccination or pathogen exposure.